Two temperature-sensitive mutations in the DNA binding subunit of EcoKI with differing properties - Janscak, P; Weiserova, M; Hubacek, J; Holubova, I; Dutta, C F; Firman, K (FEMS microbiology letters, 2000)
Two temperature-sensitive mutations in the hsdS gene, which encodes the DNA specificity subunit of the type IA restriction-modification system EcoKI, designated Sts1 (Ser(340)Phe) and Sts2 (Ala(204)Thr) had a different impact on restriction-modification functions in vitro and in vivo. The enzyme activities of the Sts1 mutant were temperature-sensitive in vitro and were reduced even at 30 degrees C (permissive temperature). Gel retardation assays revealed that the Sts1 mutant had significantly decreased DNA binding, which was temperature-sensitive. In contrast the Sts2 mutant did not show differences from the wild-type enzyme even at 42 degrees C. Unlike the HsdSts1 subunit, the HsdSts2 subunit was not able to compete with the wild-type subunit in assembly of the restriction enzyme in vivo, suggesting that the Sts2 mutation affects subunit assembly. Thus, it appears that these two mutations map two important regions in HsdS subunit responsible for DNA-protein and protein-protein interactions, respectively.
Keywords: bodová mutace; DNA Methylation; Temperature; Plasmids; DNA Restriction Enzymes; adenosintrifosfatasy; Bacterial Proteins; metylace DNA; DNA restrikčně-modifikační enzymy; Escherichia coli; restrikční enzymy; DNA, Bacterial; DNA bakterií; Point Mutation; Adenosine Triphosphatases; DNA Restriction-Modification Enzymes; bakteriální proteiny; plazmidy; teplota